Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1055/s-0034-1382995
|View full text |Cite
|
Sign up to set email alerts
|

Meroterpenes from Psoralea corylifolia against Pyricularia oryzae

Abstract: Six new meroterpenes, namely, 13-methoxyisobakuchiol (1), 13-ethoxyisobakuchiol (2), 12,13-dihydro-13-hydroxybakuchiol (3), Δ(10)-12,13-dihydro-12-(R,S)-methoxyisobakuchiol (4 and 5), and 15-demetyl-12,13-dihydro-13-ketobakuchiol (6), together with four known ones, namely, Δ(3),2-hydroxybakuchiol (7), Δ(1),3-hydroxybakuchiol (8), bakuchiol (9), and Δ(1,3)-bakuchiol (10), were isolated from the seeds of Psoralea corylifolia. Their structures were identified based on spectral data, including those obtained via 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…It is widely used to treat yang deficiency of the spleen and kidney in adult and pediatric patients in China, Korea, and Japan. Furthermore, modern pharmacological studies have confirmed that this seed exhibits potent medicinal activities like estrogenic (Liu et al, 2020), antitumor (Jin et al, 2020), anti-oxidant (Limper et al, 2013), antimicrobial (Huang et al, 2014), anti-inflammatory (Szliszka et al, 2011), antidepressant (Mao et al, 2014), and osteoblastic activities (Huang et al, 2019). However, recent clinical reports have indicated that treatment associated with PF has an increased risk of liver injury (Nam et al, 2005;Teschke and Bahre, 2009;Smith and MacDonald, 2014;Li and Huang, 2016;Li and Cheng, 2018;Zhang and Huang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used to treat yang deficiency of the spleen and kidney in adult and pediatric patients in China, Korea, and Japan. Furthermore, modern pharmacological studies have confirmed that this seed exhibits potent medicinal activities like estrogenic (Liu et al, 2020), antitumor (Jin et al, 2020), anti-oxidant (Limper et al, 2013), antimicrobial (Huang et al, 2014), anti-inflammatory (Szliszka et al, 2011), antidepressant (Mao et al, 2014), and osteoblastic activities (Huang et al, 2019). However, recent clinical reports have indicated that treatment associated with PF has an increased risk of liver injury (Nam et al, 2005;Teschke and Bahre, 2009;Smith and MacDonald, 2014;Li and Huang, 2016;Li and Cheng, 2018;Zhang and Huang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Psoralea corylifolia L. (PC), belonging to Leguminosae, is one of the most popular traditional Chinese medicines used for psoriasis and vitiligo [8,9]. Phytochemical researches show that P. corylifolia contains coumarins, flavonoids, and monoterpene phenols [10,11]. As for the polysaccharides of P. corylifolia , the studies on polysaccharides from P. corylifolia purification and their structural characteristics and biological activities for P. corylifolia polysaccharides were few, and only a few scholars have conducted preliminary studies, for example Zheng C X et al [12] initially studied the feasibility and the mechanism of the polysaccharide from P. corylifolia for the repair of articular cartilage defects in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Bakuchiol is a meroterpene, which can be found in the traditional Chinese herbal medicine Fructus Psoraleae , the dried ripe fruit of Psoralea corylifolia L. (Fabaceae). It is shown to have anti-microbial, anti-inflammatory, anti-oxidative, anti-osteoporosis, and anti-depression or anti-stress activities ( Lim et al, 2009 ; Choi et al, 2010 ; Kim et al, 2013 ; Huang et al, 2014 ; Mao et al, 2014 ). The estrogenic activities of bakuchiol were reported in several in vitro models ( Xin et al, 2010 ; Lim et al, 2011 ; Mao et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%